2018
DOI: 10.1016/j.cmi.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of carbapenem-resistant Acinetobacter nosocomialis strain ST410 harbouring plasmid-borne blaOXA-72 gene in Taiwan

Abstract: Letter to the Editor Emergence of carbapenem-resistant Acinetobacter nosocomialis strain ST410 harbouring plasmid-borne bla OXA-72 gene in Taiwan Acinetobacter nosocomialis is increasingly identified as a causative agent of nosocomial infections in recent years [1]. Carbapenems, especially imipenem, is often used as the drug of choice for treating multidrug-resistant Gram-negative bacterial infection, but the carbapenem-nonsusceptible rate of the Acinetobacter species is increasing worldwide. The Ambler class … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
2
6
0
Order By: Relevance
“…Further studies confirmed that AdeRS TCS played a role in the resistance to the three antibiotics in A. nosocomialis. ST410 was found to be the most dominant type in clinical Tn-CRAn isolates in Taiwan, which is consistent with our previous studies (Chen et al, 2018;Yang et al, 2019). This may indicate that there is an unknown mechanism in ST410 that provides fitness advantage in a hospital setting, which could easily transform to carbapenem and/or tigecycline resistance.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Further studies confirmed that AdeRS TCS played a role in the resistance to the three antibiotics in A. nosocomialis. ST410 was found to be the most dominant type in clinical Tn-CRAn isolates in Taiwan, which is consistent with our previous studies (Chen et al, 2018;Yang et al, 2019). This may indicate that there is an unknown mechanism in ST410 that provides fitness advantage in a hospital setting, which could easily transform to carbapenem and/or tigecycline resistance.…”
Section: Discussionsupporting
confidence: 89%
“…Acinetobacter nosocomialis is an emerging opportunistic pathogen that is usually grouped into the Acinetobacter calcoaceticus-baumannii complex (Acb complex) (Vijayakumar et al, 2019). In Asia, the carbapenem resistant rate among infections caused by A. nosocomialis is as high as 30% (Chen et al, 2018;Singkham-In and Chatsuwan, 2018;Chen et al, 2019). Tigecycline has been regarded as one of the final armamentaria against carbapenem resistant A. nosocomialis (CRAn).…”
Section: Introductionmentioning
confidence: 99%
“…Plasmid pAB-NCGM253, which carries bla OXA-72 , was recently identified in carbapenem-resistant A. nosocomialis isolates in Taiwan (20). PCR mapping showed that all seven A.…”
Section: Resultsmentioning
confidence: 99%
“…ST410 was first registered in the MLST database as CRAN in 2012. In our previous research [22], Pasteur ST410 was demonstrated to carry plasmid-borne bla OXA-72 ( bla OXA-24 subgroup). In this study, we found that these CRAN ST410 isolates carrying the bla OXA-24 subgroup gene were mainly Oxford ST1997.…”
Section: Discussionmentioning
confidence: 99%